Radiology Perspective One-Year Study of Hirschsprung Disease - Tjan, Anastasia (Folia Medica Indonesiana, 2021)
Hirschsprung disease is a rare developmental disorder of the enteric nervous system. This researched purpose to give an epidemiological database and current trend analysis from radiological perspective of Hirschsprung disease at our center. A prospective descriptive study was conducted for a year in 2017 at Sanglah Public General Hospital Bali. Colon in loop examination using either water-soluble or barium was conducted. All baseline characteristics, contras media used, and HD type were the parameter being evaluated in this study. Hirschsprung accounted for 2.16% from all 1018 newborn. Male is 3.4 times more prone to Hirschsprung disease. Age distribution predominant during 0 – 4 weeks after birth (36.4%). Ultrashort, short, long segments were 45.5%, 45.5%, and 9% respectively. Contras media used was mainly barium rather than water soluble 8:3, due to standard operating procedure adapted by some pediatric surgeon. Ultrashort and short segment HD has the same contribution. Barium is dominated at our center although water soluble is chosen in most literature for infant, due to its ability as diagnostic as well as therapeutic. Hence further research should be done to support and change the perspective in making the diagnosis.